Preparation and characterization of mono- and multilayer films of polymerizable 1,2-polybutadiene using the Langmuir-Blodgett technique - Hitrik, Maria; Gutkin, Vitaly; Lev, Ovadia; Mandler, Daniel (LangmuirLangmuir : the ACS journal of surfaces and colloids, 2011)
The essence of this study is to apply the Langmuir-Blodgett (LB) technique for assembling asymmetric membranes. Accordingly, Langmuir films of a (further) polymerizable polymer, 1,2-polybutadiene (1,2-pbd), were studied and transferred onto different solid supports, such as gold, indium tin oxide (ITO), and silicon. The layers were characterized both at the air/water interface as well as on different substrates using numerous methods including cyclic voltammetry, impedance spectroscopy, spectroscopic ellipsometry, atomic force microscopy, X-ray photoelectron spectroscopy, and reflection-absorption Fourier transform infrared spectroscopy. The Langmuir films were stable at the air-water interface as long as they were not exposed to UV irradiation. The LB films formed disorganized layers, which gradually blocked the permeation of different species with increasing the number of deposited layers. The thickness was ca. 4-7 Å per layer. Irradiating the Langmuir films caused their cross-linking at the air-water interface. Furthermore, we took advantage of the reactivity of the double bond of the LB films on the solid supports and graft polymerized acrylic acid on top of the 1,2-pbd layers. This approach is the basis of the formation of an asymmetric membrane that requires different porosity on both of its sides.[on SciFinder (R)]
MEDLINE AN 2011862264(Journal; Article; (JOURNAL ARTICLE))